Hipnoterapi Sebagai Media Psikologis Bagi Penderita Asma - Lenny Utama Afriyenti (Syntax Idea)
There are several types of psychotherapy used by psychologists, one of which is popular is the hypnotherapy method. Hypnotherapy with hypnosis is a therapy that has high effectiveness. Patients with various types of diseases can be helped by this method. One of them is asthma which is a medical disease. This study aims to see the effectiveness of the benefits of hypnotherapy for asthma patients. The steps taken are pre-induction talk, induction, deepening, suggestion, therapy, termination and verbalization. In the use of hypnotherapy also perform part therapy techniques, object imagery and forgiveness for 45 minute. PHQ-9 as a predictor for depresive. Descriptively, there were changes felt by asthma patients with five meetings of hypnotherapy. Breathing becomes more relieved and you can regulate your breath if you feel shortness of breath.